IMPLEMENTATION OF FINANCIAL MANAGEMENT ACCOUNTING INFORMATION SYSTEM - Ira Yuliana Wakum; Tia Ramadanis; Hadi Supratikta (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
This qualitative research discusses the implementation of the Financial Management Accounting Information System (FIS) and its implications for the efficiency and effectiveness of financial management of organizations or companies. Through a case study approach, this research analyzes how the implementation of AIS-PK affects the sprocess of recording, monitoring, and reporting finances. Data were obtained through interviews with relevant personnel, direct observation, and analysis of finance-related documents. The results show that the implementation of AIS-PK positively affects the efficiency of financial management by improving accuracy and speed in recording transactions and monitoring cash. In addition, the ability to generate real-time financial reports also strengthens more timely decision-making. The implication of these findings is the importance of information technology integration in financial management strategies to improve organizational or corporate performance